Nanotechnology Based Approaches in Phage Therapy: Overcoming the Pharmacological Barriers - Kaur, Sandeep; Kumari, Anila; Kumari Negi, Anjana; Galav, Vikas; Thakur, Shikha; Agrawal, Manish; Sharma, Vandana (Frontiers in Pharmacology, 2021)
With the emergence and spread of global antibiotic resistance and the need for searching for safer alternatives, there has been a resurgence in exploring the use of bacteriophages in the treatment of bacterial infections referred to as phage therapy. But the fact remains that to date, phage therapy has not received regulatory approval for human use (except for compassionate use). Thus, to hit the clinical market, the roadblocks need to be seriously addressed with modern solution-based technologies. Nanotechnology represents one such ideal and powerful tool for overcoming the pharmacological barriers of administered phage preparations. In literature, there are many review articles on nanotechnology and bacteriophages but these are primarily focused on highlighting the use of phages in different fields of nano-medicine. Reviews specifically focused on the use of nanotechnology-driven techniques strictly to improve phage therapy are however limited. The present review gives a detailed insight into the more recent strategies which include a) use of lipid-based nano-carriers (liposomes, transfersomes etc.) b) adopting the microfluidic-based approach, surface modification methods to further enhance the efficiency and stability of phage loaded liposomes b) Nano- emulsification approach with the integration of microfluidics for producing multiple emulsions (suitable for phage cocktails) with unique control over size, shape and drop morphology c) Phage loaded nanofibers produced by electro-spinning and advanced core-shell nanofibers for immediate, biphasic and delayed-release systems and d) Smart release drug delivery platforms that allow superior control overdosing and phage release as and when required. All these new advances are aimed at creating a suitable housing system for therapeutic bacteriophage preparations while targeting the multiple issues of phage therapy i.e improving phage stability and titers, improving in-vivo retention times, acting as suitable delivery systems for sustained release at the target site of infection, improved penetration into biofilms and protection from immune cell attack. The present review thus aims at giving a complete insight into the recent advances related to various nanotechnology-based approaches to address the issues pertaining to phage therapy. This is essential for improving the overall therapeutic index of success of phage therapy for future clinical approval.